2012
DOI: 10.1177/155892501200700203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycra Extension Percent on Single Jersey Knitted Fabric Properties

Abstract: This research studies the effect of extension increase percent of bare Lycra yarns during loop formation on the geometrical, physical and mechanical properties of plain jersey fabrics. Samples with 100% cotton yarns, Lycra yarns in alternating courses (half plating) and Lycra yarns in every course (full plating) were produced on a circular knitting machine. The two latter cases were produced at five different levels of Lycra extension. Thermal setting was carried out without any traverse tension during finishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…As the Lycra extension percent reached 232% in the case of the half plating fabrics, the course density increased by 40% and the wale density increased by 6% [14][15][16]. The results obtained in the present work indicated that the amount of elastane has a significant effect on dimensional and elastic properties of cotton/elastane plated plain knitted fabric [17].…”
Section: Introductionsupporting
confidence: 47%
“…As the Lycra extension percent reached 232% in the case of the half plating fabrics, the course density increased by 40% and the wale density increased by 6% [14][15][16]. The results obtained in the present work indicated that the amount of elastane has a significant effect on dimensional and elastic properties of cotton/elastane plated plain knitted fabric [17].…”
Section: Introductionsupporting
confidence: 47%
“…The results show that the extension values of the selected knit structures are higher than necessary values and residual extension values are lower full plated fabrics. and Sadek [28]. Air permeability is lowest for full plating knit fabrics because of tighter structures and smaller pore sizes are obtained with full plaited knit fabrics.…”
Section: Elastic Properties Of Cotton/elastane Knitted Fabricsmentioning
confidence: 96%
“…Sadek et al [6] studied the effect of Lycra percent on single jersey properties. As the Lycra extension percent reached 232% in the case of the half plating fabrics, the course density increased by 40%, the wale density increased by 6%, the thickness increased by 25%, the air permeability decreased by 78%, and the initial elasticity modulus decreased by 55%.…”
Section: Introductionmentioning
confidence: 99%